حديقة التراث الفلسطيني - عطاونة, محمد; شاهين, محمد; عطاونة, محمد (جامعة بوليتكنك فلسطين - معماري, 2011)
يتعرض الشعب الفلسطيني لكثير من عمليات السلب والتهويد لذلك تم اقتراح عمل دراسة لحديقة التراث الفلسطيني لتكون بادرة للصد على ما بتعرض عليه هذا الشعب بحيث يكون سجلا ملموسا لمشاهد شتى من تراث الشعب الفلسطيني، وكثير من المقومات والعناصر التراثية الفلسطينية على مر الزمن. يهدف هذا البحث إلى إعداد دراسة لتصميم حديقة تراثية تمثل دعوة لإنهاض هذا التراث وصقله في نفس المواطن الفلسطيني من اجل حمايته من الاندثار ومنع عمليات التهويد التي يمارسها الاحتلال الصهيوني وغيره من الجمعيات المستشرقة على الإرث الفلسطيني وذلك بتعريف المواطن الفلسطيني بإرثه ، وإعادة إحياء حس الحياة الفلسطينية القديمة في نفس الفلسطينيين . ولتحقيق ذلك اعتمدت الدراسة على المنهج الوصفي التحليلي القائم على الحالة الدراسية والاتصال ببعض الأشخاص الذين لديهم الخبرة في هذا المشروع ، والمقابلات الشخصية وزيارة بعض الأماكن ذات الصلة بهذه الدراسة ، والاستعانة ببعض الكتب والمجلات والوثائق ذات العلاقة ، وزيارة الجمعيات والمؤسسات التي تعنى بالتراث الفلسطيني والاستعانة بهذه المعلومات كخلفية نظرية للقيام بعملية التخطيط والتصميم . يعتمد المشروع المقترح في الأساس على إظهار التراث الفلسطيني، سواء أكان تراث مادي أو فكري أو فني، بحيث تكون الوظيفة الأساسية فيه جذب اهتمام الزائر ليتعرف على حضارة وعناصر تراثية مرئية ليتمكن من أخذ فكرة متكاملة عنها . وبالتالي فان النتيجة المرجوة من هذا المشروع التخطيطي والتصميمي هو إيجاد سجلا تراثيا بشكل مرئي للمشاهد، ليتحقق بذلك التواصل ما بين الماضي والحاضر والمستقبل، لتكون هذه الحديقة رمزا للمحافظة على التراث . Abstract The Palestinian people face many of the looting and the conversion. For this reason, a proposed study for constructing a Palestinian heritage park takes its place here to be a gesture to repel what exposure upon this people, and to be a significant scenes record of the heritage of the Palestinian people, and many of the traditional Palestinian components and elements over time. This research aims to prepare a study to design a heritage park represents a call to reveille this heritage and refined it within the Palestinian citizen themselves in order to protect it from extinction and prevent the conversion practiced by the Zionist occupation and other oriental associations on Palestine's legacy by showing the Palestinians their heritage, and reviving a sense of Palestinian life. To achieve this, the study relied on a descriptive analytical method based on case study, contacting some people who have experience in this discipline, personal interviews, visits to some places relevant to this study, the use of some books, magazines and related documents, and visits to the associations and institutions concerned with the Palestinian heritage of, and the use of theoretical information as a background to carry out the planning and design of the project. The proposed project basis primarily on representing the Palestinian heritage, whether it was physical, intellectual or artistic. So, the primary proposed function of is the attract of the visitor attention to learn about the culture and heritage visible elements to be able to take an integrated idea about them. Thus, the desired outcome of this planning and design project is to create a record of visible heritage for the viewer, to achieve the continuity between past, present and future, and to be a symbolic park to preserve heritage.
no of pages 80, 12597, معماري 7/2011 , in the store
Keywords: الحدائق التراثية - تصميم